Social ethics in Korea: social challenges from the perspective of young people = han gug ui sa hoe yun li : cheong nyeon ui si gag eu lo bon sa hoe jeog do jeon gwa je - Seo, Lee Yeong (Working paper, 2023)
This working paper contains a collection of essays by young Koreans who reflect normatively on the social and political problems in their homeland. These are topics where Christian social ethics can also provide normative orientation to shape a just Korean society. Against the backdrop of the country's rapid development, the introductory reflections briefly outline South Korea's current political and socioeconomic situation with a particular focus on young people. It shows the societal context in broad strokes in which the essays deal with social issues chosen by the young writers themselves. This working paper thus aims to make a small contribution to the German-Korean dialogue on social ethical issues.